Oxidative Activation of Bagasse Fibers Surfaces in Medium Density Fiberboard Manufacturing - Doosthoseini (University of Zagreb, Faculty of Forestry and Wood Technology, 2013)
This study presents the investigation of the effects of oxidant type (nitric acid and potassium dichromate), oxidant content (three different levels as 2, 4, and 6 percent) and urea- formaldehyde (UF) resin percentage (two levels as 5 and 7 percent) on mechanical and physical properties of interior grade medium density fiberboard made from bagasse fibers. Some panel properties were studied, such as modulus of rupture (MOR) and modulus of elasticity (MOE) in bending, compression-shear strength (C.S sth.), water absorption (WA) and thickness swelling (TS) after 2- and 24-hour immersion in cold water. In addition, the results indicated the best values for WA and TS after 2- and 24-hour immersion, and C.S. sth. was discerned at 7 percent UF resin content, together with 6 percent nitric acid. Furthermore, the greatest values for MOR and MOE were related to 7 percent UF resin content together with 4 percent nitric acid.